A comparison of delayed SIR and SEIR epidemic models - Abdelilah Kaddar; Abdelhadi Abta; Hamad Talibi Alaoui (Nonlinear Analysis, 2011)
In epidemiological research literatures, a latent or incubation period can be medelled by incorporating it as a delay effect (delayed SIR models), or by introducing an exposed class (SEIR models). In this paper we propose a comparison of a delayed SIR model and its corresponding SEIR model in terms of local stability. Also some numerical simulations are given to illustrate the theoretical results.